2011
DOI: 10.1007/s00467-011-1945-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dialysis solution biocompatibility on ultrafiltration and on free water transport in rats

Abstract: This study compares different peritoneal dialysis fluids (PDF) in rats over a short contact time. For greater accuracy, net ultrafiltration (UF) and peritoneal transport indices, mass transfer area coefficient (MTAC) were scaled for the in vivo peritoneal surface area recruited (ivPSA) measured by microcomputerized tomography. Wistar rats underwent nephrectomy (5/6ths), were randomized into two groups and given 1.5% glucose PDF, either conventional acidic lactate (n = 14) or pH neutral bicarbonate (BicaVera) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In the present study, we used agomir which was a class of chemically engineered oligonucleotides act as mimic of microRNA to overexpress the level of miR-200a in rats model of PD, we proved that agomir-miR-200a was capable of intervening in progressive PF and protecting of functional injury. Though the changes in D/D0 have not shown the statistical significance, it may be associated with individual variation in the glucose metabolic rate and solute transport efficiency, which was consistent with previous studies in human and animal [ 25 ]. Furthermore, it was shown that up-regulated miR-200a was associated with down-regulation of ZEB1/2 and inhibition of EMT, which was consistent with our previous study in vitro.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we used agomir which was a class of chemically engineered oligonucleotides act as mimic of microRNA to overexpress the level of miR-200a in rats model of PD, we proved that agomir-miR-200a was capable of intervening in progressive PF and protecting of functional injury. Though the changes in D/D0 have not shown the statistical significance, it may be associated with individual variation in the glucose metabolic rate and solute transport efficiency, which was consistent with previous studies in human and animal [ 25 ]. Furthermore, it was shown that up-regulated miR-200a was associated with down-regulation of ZEB1/2 and inhibition of EMT, which was consistent with our previous study in vitro.…”
Section: Discussionsupporting
confidence: 89%
“…This may be associated with individual variation in the glucose metabolic rate and solute transport efficiency, as previously described in human and animal studies. 30,31 Furthermore, we found that the protective effect of miR-30a on peritoneal fibrosis was also associated with the blockade of EMT, as demonstrated by preventing the loss of epithelial and mesothelial markers, including E-cad and cytokeratin-18, and the gain of a mesenchymal marker, a-SMA, resulting in inhibition of peritoneal collagen matrix accumulation (Figure 7, A and B). Similar to the results seen in an in vitro study, the therapeutic effect of miR-30a on peritoneal fibrosis in vivo was also associated with the inhibition of Snai1 (Figure 7, B and F).…”
Section: Mir-30a Inhibits Peritoneal Fibrosismentioning
confidence: 90%
“…Ultrafiltration extracts the interstitial fluid by employing the negative pressure provided by a vacuum, which does not dilute the interstitial fluid and therefore can be used to obtain the interstitial glucose concentration directly. However, it is difficult to operate on the human body due to the ultrafiltration probe being too long, and can only be used in animal testing [31][32][33]. Hence, ultrafiltration cannot be used in experimental evaluations of non-invasive and minimally invasive blood glucose monitoring techniques in the human body.…”
Section: Selection Of Microdialysis Calibration Methodsmentioning
confidence: 99%